Assembly of a miRNA‐modified QCM sensor for miRNA recognition through response patterns. Issue 5 (6th December 2018) - Li, Xue; Ma, Ding; Zheng, Sheng‐Run; Fan, Jun; Wang, Tai; Dai, Zong; Zou, Xiao‐Yong; Teng, Shao‐Hua; Zhang, Wei‐Guang
Abstract: In this paper, a miRNA‐based quartz crystal microbalance (QCM) biosensor was fabricated and used to the rapid and effective sensing of miRNA. The specific hybridization between probe miRNA and different selected miRNAs (miR‐27a, miR‐27b, and Let‐7a) cause a different interaction mode, thus display different frequency change and response patterns in the QCM sensor, which were used to detect miR‐27a and miR‐27b. The selective sensing of miR‐27a in mixed miRNA solution was also achieved. This miRNA‐based QCM biosensor has the advantages of real‐time, label‐free, and short cycle detection. Abstract : A miRNA‐based quartz crystal microbalance (QCM) biosensor was fabricated and used to the rapid and effective sensing of miRNA .